INTRODUCTION TO ALEXANDER GAVRILOV’S "HUMANISM AS ANTI-IDEOLOGY" - Adams, Hazard (Surfaces, 2001)
In the context of the Third International Conference on Humanistic Discourse, this text summarizes the introduction to Alexander Gavrilov’s "Humanism as Anti-Ideology" that Hazard Adams delivered and reports on the central concerns that emerged in its discussion.